2005
DOI: 10.1590/s1414-98932005000200002
|View full text |Cite
|
Sign up to set email alerts
|

As relações de gênero e as percepções dos/das motoristas no âmbito do sistema de trânsito

Abstract: Este artigo teve o propósito de estudar não só as relações de gênero no âmbito do sistema de trânsito, pesquisando como a mulher motorista e o homem motorista percebem e compreendem a si mesmo e ao outro sexo, bem como o de investigar as representações sociais existentes. Participaram da pesquisa 84 motoristas, com faixa etária de 18 a 60 anos de idade, sendo 42 do sexo feminino e 42 do sexo masculino. A coleta dos dados foi realizada através de contatos com homens e mulheres em universidades, locais de trabal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
0
2
0
5
Order By: Relevance
“…Investigating perceptions about drivers, in Recife, in 2005, Almeida et al 14 identified that female drivers tend to perceive themselves and to be perceived by men as prudent, attentive and cautious, with a tendency to obey traffic rules, practicing a more defensive direction, with a greater vision of danger and causing fewer accidents. On the other hand, they are also seen as slow, insecure and dangerous drivers.…”
Section: Gendermentioning
confidence: 99%
See 1 more Smart Citation
“…Investigating perceptions about drivers, in Recife, in 2005, Almeida et al 14 identified that female drivers tend to perceive themselves and to be perceived by men as prudent, attentive and cautious, with a tendency to obey traffic rules, practicing a more defensive direction, with a greater vision of danger and causing fewer accidents. On the other hand, they are also seen as slow, insecure and dangerous drivers.…”
Section: Gendermentioning
confidence: 99%
“…Such policies must take into account the social relationships that involve this reality: urban mobility patterns that privilege individual transportation; road network with conservation problems; social hierarchization of streets and traffic 10 ; traffic as an assertion of power and gender bias 14 ; labor market whose tele-delivery and transportation sector employs black and brown young people with little schooling, but subject them to death risks [23][24][25] ; worker health and corpo- rate/market accountability for prevention 21 ; and pre-hospital care to RTA victims 31 . Thus, such policies must have intersectoral characteristics, articulating at least protective measures for transit workers; expansion and focus of worker health programs for this audience; intense and constant preventive and educational actions about alcohol and drugs use while driving; programs to fight against gender discrimination; actions to regulate vehicle advertising that exalt aggressive driver behavior; a national road and highway quality policy; and mobilization of civil society for a change in the way people behave in traffic.…”
Section: Mortality Due To Traffic Accidents In Brazil: 1996 To 2015mentioning
confidence: 99%
“…Segundo Almeida et al (2005), não é possível se estudar o trânsito sem discutir questões de gênero, escolaridade e o nível socioeconômico. No que se refere ao gênero, por exemplo, os autores afirmam que existem diferenças nos papéis sociais de homens e mulheres motoristas e em suas relações com o trânsito.…”
Section: Resultsunclassified
“…Apesar disso, os dados do presente estudo sinalizam que os homens estão vivendo menos anos com incapacidades do que as mulheres, o que pode ser explicado pelos estereótipos e valores no trânsito presentes no imaginário popular, de que homens são imprudentes e ameaçadores para o trânsito, porém mais seguros ao volante. O fato de as mulheres serem vistas como prudentes, obedientes e cautelosas pode explicar porque elas vivem mais anos com incapacidade por seus acidentes, que tendem a ter menor gravidade 19, 25 .…”
Section: Discussõesunclassified